Analisis partisipasi masyarakat terhadap pengelolaan sampah di Kecamatan Sumbersari, Kabupaten Jember, Provinsi Jawa Timur - Wijayanti, Aprilia Nur; Dhokhikah, Yeny; Rohman, Abdur (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Solid waste is left over from human activities that is no longer used by humans. The problem of waste is the responsibility of all communities, not only the responsibility of the government. The role of the community is very important in overcoming the waste problem. This study aims to determine the waste generation and composition, community participation, and the strategies in waste management in Sumbersari District, Jember Regency, East Java Province. Data collection techniques are through sampling of waste generation and questionnaires. Sampling of 45 families in Sumbersari Village, Tegalgede Village and Antirogo Village based on the level of population density. The result of measuring household waste generation for 8 consecutive days is 299.794 kg/day (0.21kg/person/day). The community know and agree to waste management, but it is contrary to the community proportional to behavior that rarely does it. The strategy to increase community participation is to disseminate information related to the application of 3R principles, training on the use of waste into products of economic value, increasing the number of waste banks and increasing environmental activists or environmental cadres